Damage assessment through changes in mode shapes due to non-proportional damping. (June 2015) - Iezzi, F; Spina, D; Valente, C
Abstract: Modal parameters are often used for the structural damage assessment in the dynamic field. Usually, the changes in the modal parameters between different states are assumed as measures of damage. The frequencies are easy to identify, but in some circumstances they are not sensitive to damage and moreover they are mainly a global measure. On the contrary, the mode shapes are more suited for damage localization, but they are generally hard to identify accurately. The energy dissipation, and hence the damping, increases with damage. This feature is stable and has a monotonic behaviour, therefore, damping can be confidently used as an alternative or complementary measure for damage assessment in spite of the accuracy of its identification. However, the damping by itself suffers of the same drawbacks as the frequencies. The joint use of damping and mode shapes is an effective procedure for the damage identification. In the real world the damping is of nonproportional type and the measured mode shapes are complex. It is assumed that an increase of damage causes a modification of non-proportional damping and a variation of the modal complexity. The extent of modal complexity between two different structural states can be used to identify the damage through appropriate indicators. A number of such indicators is introduced and discussed. The effectiveness and sensitivity of the damage indicators are tested on theoretical and pseudo-experimental data.